Images of India in the Lithuanian press of Catholic missions, 1927–1940 - Laurynas Kudijanovas (Lietuvos Istorijos Studijos)
The article presents the perception of Indian culture and everyday life, formed by the interwar Lithuanian press of the Catholic missions, which received little attention in historiography. Based on the articles published in the Jesuit magazine “Misijos” and the Salesian magazine “Saleziečių žinios” in 3rd and 4th decades of the 20th century, three main images that represented India in Lithuania are examined: Indian spirituality and religiosity, social problems of society, primarily the caste system and women’s rights, and finally the ferocious nature of the land. The analysis of periodicals revealed that the creation of images of India was influenced by the Christian tradition, the European orientalist attitude and the comparison of East-West civilizations.